Study of the vertical distribution of radium in NORM-contaminated soil at the site of crude oil tanks in Banias - غـفر, محـمـــد (Latakia University Journal -Basic Sciences Series, 2022)
Large quantities of produced water are disposed of in the earthen basins of crude oil tanks in Banias. The random disposal of this water has been going on for decades. As a result, the deposits of naturally occurring radioactive elements (NORM) increase in the environment, which involves environmental and health risks as a result of the possibility of soil and water contamination with these elements in the region. The work aims to study the vertical and cumulative diffusion of radium in the soil affected by the produced water and to estimate the volume of soil contamination with this radioactive element. The sampling sites were selected after a radioactive survey of the area. the radioactivity concentrations of radium in soil samples were determined by gamma spectroscopy using high purity germanium (HPGe) detector. The study concluded that there is a rise in the concentration of radium radioactivity in the surface and sub-surface layers of the soil affected by the produced water in the study area, the cumulative values of radioactivity concentration and the radium depth profile in the soil indicate a vertical migration of radium from the surface to the depth. The volume of soil contamination that needs to be treated on-site has reached 25 cm, with relatively high values was ​​recorded at 50 cm depth.